Chromium-free passivating agent for copper foil used in lithium batteries and its application

Through the use of chromium-free passivator for copper foil for lithium batteries, the synergistic effect of cyclohexanhexanol hexafluoric acid, glucose and inositol (1,4,5) triphosphate is used to form a network structure with high cross-link density. The problems of poor conductivity and insufficient salt spray resistance of chromium oxide layer in the prior art were solved, and the high-temperature oxidation resistance and salt spray resistance of electrolytic copper foil were significantly improved, while ensuring the environmental protection of the process and good conductivity. .

CN116103643BActive Publication Date: 2025-02-07GUANGZHOU XUQI MATERIAL TECH CO LTD

Patent Information

Application Number
CN202211641015.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-20
Publication Date
2025-02-07
Estimated Expiration
2042-12-20

AI Technical Summary

Technical Problem

In the existing electrolytic copper foil passivation method, there are cracks in the chromium oxide layer, resulting in poor conductivity and containing the carcinogenic substance chromium, which pollutes the environment. At the same time, the prior art has failed to effectively improve the salt spray resistance of electrolytic copper foil.

Method used

A copper foil chromium-free passivation agent for lithium batteries is used. This agent is composed of main salt, organic acid, corrosion inhibitor, chelating agent, complexing agent, additive and organic solvent. A stable passivation film is generated through stirring reaction. The specific formula includes the synergistic effect of cyclohexanhexanol hexaphosphate, glucose and inositol (1,4,5) triphosphate of 40% mass fraction to form a network structure with high crosslink density.

Benefits of technology

The formed passivation film has good conductivity, can keep the surface bright and unchanged at a high temperature of 140°C, and is left in 10% salt spray for 72 hours without light brown spots, which significantly improves the high temperature resistance and oxidation resistance of electrolytic copper foil. It also has anti-salt spray properties, while avoiding the use of toxic substances, and the process is simple and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116103643B_ABST
    Figure CN116103643B_ABST
Patent Text Reader

Abstract

The invention discloses a chromium-free copper foil passivator for lithium batteries and application thereof. The preparation raw materials thereof include: a main salt, an organic acid, a corrosion inhibitor, a chelating agent, a complexing agent, an additive and an organic solvent. In addition, inositol substances are also included. Under the synergistic effect of cyclohexane hexaphosphate, glucose and inositol (1,4,5) triphosphate, the salt spray resistance and oxidation resistance of 6-10μm double-glazed copper foil are greatly improved, the conductive property is good, the copper foil can be applied to the field of lithium ion batteries, no toxic substances such as chromium, arsenic and selenium are used, the process is simple, the copper foil is environmentally friendly, the production cost is reduced, and sustainable development is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface treatment of electrolytic copper foil, and its classification number is C25D3 / 00. Specifically, it relates to a chromium-free passivating agent for copper foil specially used for lithium batteries and application thereof. Background Art

[0002] Electrolytic copper foil is the basic conductive raw material for the production of printed circuit boards and lithium-ion batteries, and is the carrier for the mutual assembly of various electronic components. In recent years, with the upgrading of electronic technology and mobile communications at home and abroad, electronic circuit boards are developing in the direction of complete varieties, diversified functions, and rapid transmission. The production and application of electrolytic copper foil are also gradually developing towards refinement, ultra-thinness, and high frequency. Since the raw foil prepared by electrodeposition is copper crystal grains with exposed surface, it has poor resistance to high-temperature oxidation and is prone to copper diffusion, resulting in the risk of short circuit in the later printed circuit board; directly etching the circuit with raw foil is also prone to side corrosion, resulting in the risk of short circuit. Therefore, in the actual production and application of printed circuit boards, electrolytic copper foil needs to undergo a series of surface treatments, usually including pretreatment, roughening, curing, alloying, passivation, and silanization processes to meet the application requirements of various emerging components.

[0003] At present, the main method of electrolytic copper foil passivation is to use chromic acid solution to generate a chromium oxide protective layer, but there are many cracks in the chromium oxide layer, and then a layer of zinc or zinc alloy is plated under the chromium oxide layer to improve its high-temperature oxidation resistance. However, the process is relatively complicated, and the chromium oxide layer is a semiconductor, which will increase the resistance of the copper foil and deteriorate its conductivity. In addition, chromium is a carcinogen, which will not only harm the human body, but also pollute the environment. In the lithium-ion battery industry, the passivation layer needs to have the characteristics of low internal resistance, strong corrosion resistance and good high-temperature oxidation resistance.

[0004] Chinese patent CN101532154B discloses a chromium-free passivation treatment method for the surface of electrolytic copper foil. The invention can make the electrolytic copper foil product free of oxidation under high temperature conditions of 220°C for 30 minutes. Although it solves its high temperature resistance and oxidation resistance, the salt spray resistance of the electrolytic copper foil product needs to be improved. In addition, the conductive performance of the electrolytic copper foil after passivation is also very important, but this patent does not solve it. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present invention provides a chromium-free passivator for copper foil of lithium battery, the raw materials for preparing the passivator include: main salt, organic acid, corrosion inhibitor, chelating agent, complexing agent, additive and organic solvent.

[0006] Further preferably, the corrosion inhibitor is diethanolamine, the chelating agent includes at least one of hydroxyethylidene diphosphonic acid, nitrilotriacetic acid, aminotrimethylene phosphoric acid, hydroxyacetic acid, methylene diphosphonic acid and ethylenediaminetetramethylene phosphoric acid; and the organic solvent is at least one of ethylene glycol, polyethylene glycol, ethylene glycol, fatty amine polyoxyethylene ether and alkylphenol polyoxyethylene ether.

[0007] Further preferably, the complexing agent is hydroxyethylidene diphosphonic acid, and the organic solvent is polyethylene glycol.

[0008] Further preferably, the mass concentration of the hydroxyethylidene diphosphonic acid is 0.1-2 g / L, the polyethylene glycol is polyethylene glycol 200, and its mass concentration is 5-15 g / L, and the mass concentration of the corrosion inhibitor is 0.5-6 g / L.

[0009] Further preferably, the mass concentration of the hydroxyethylidene diphosphonic acid is 0.2 g / L, the mass concentration of the polyethylene glycol 200 is 10 g / L, and the mass concentration of the corrosion inhibitor is 4 g / L.

[0010] Preferably, the main salt includes at least one of molybdate, silicate, phosphate, titanium salt, nickel salt and zirconium salt.

[0011] Further preferably, the main salt includes at least one of silicate, nickel salt and molybdate.

[0012] Further preferably, the main salt is silicate, and the silicate is sodium silicate solution.

[0013] Further preferably, the mass fraction of the sodium silicate solution is 50-60%, and the mass concentration is 10-20 g / L.

[0014] Further preferably, the mass fraction of the sodium silicate solution is 60% and the mass concentration is 15 g / L.

[0015] Preferably, the organic acid includes at least one of formic acid, oxalic acid, organophosphorus compounds, citric acid, ascorbic acid, tartaric acid and malic acid.

[0016] Further preferably, the organic acid is an organophosphorus compound, the organophosphorus compound is a cyclohexanehexol hexaphosphate solution, and the mass fraction of the cyclohexanehexol hexaphosphate solution is 30-40%.

[0017] Further preferably, the mass concentration of the cyclohexanehexol hexaphosphate solution is 15-20 mL / L, and the mass fraction is 40%.

[0018] Further preferably, the mass concentration of the cyclohexanehexol hexaphosphate solution is 18 mL / L, and the mass fraction is 40%.

[0019] Preferably, the raw materials for preparing the chromium-free passivator for copper foil used for lithium batteries also include inositol substances.

[0020] Preferably, the inositol substances account for 20-30% of the mass concentration of the organic acid.

[0021] Further preferably, the inositol substances account for 23-26% of the mass concentration of the organic acid.

[0022] Further preferably, the inositol substances account for 25% of the mass concentration of the organic acid.

[0023] Preferably, the inositol substance is inositol (1,4,5) triphosphate.

[0024] Preferably, the chelating agent includes at least one of benzotriazole, ethylenediaminetetraacetic acid, sodium gluconate, trisodium nitrilotriacetate and sodium trimethylenephosphonate.

[0025] Further preferably, the chelating agent is sodium gluconate, and the mass concentration of the sodium gluconate is 2-10 g / L.

[0026] Further preferably, the mass concentration of the sodium gluconate is 5 g / L.

[0027] Preferably, the additive is at least one of polyhydroxy aldehyde, nano silica sol, thiourea and hydrochloric acid.

[0028] Further preferably, the additive is a polyhydroxy aldehyde, and the polyhydroxy aldehyde is glucose.

[0029] Further preferably, the mass concentration of glucose is 1-10 g / L.

[0030] Further preferably, the mass concentration of the glucose is 2-6 g / L.

[0031] Further preferably, the mass concentration of glucose is 4 g / L.

[0032] Preferably, the additive further includes zinc oxide.

[0033] Further preferably, the mass concentration of the zinc oxide is 1-3 g / L.

[0034] Further preferably, the mass concentration of zinc oxide is 2 g / L.

[0035] The preparation method of the chromium-free passivating agent for copper foil of lithium battery is as follows:

[0036] The main salt, organic acid, corrosion inhibitor, chelating agent, complexing agent, additive and organic solvent are added into the reaction kettle, and the stirring speed is 350-500 rpm / min and the stirring time is 30-60 min to obtain the product.

[0037] The applicant found that the addition of 40% by mass of cyclohexane hexaphosphate solution and polyhydroxy aldehyde enhanced the salt spray resistance and antioxidant properties of the passivation film. The reason may be that the phosphorus hydroxyl groups that did not participate in the reaction of the cyclohexane hexaphosphate solution can be connected by hydrogen bonds or dehydration reactions to form a phytic acid passivation film with a high cross-linking density and a network structure. After adding polyhydroxy aldehydes, especially when the polyhydroxy aldehyde is glucose, the copper alloy surface is made denser. However, the addition of only cyclohexane hexaphosphate solution and glucose will affect the 6-10μm double-glazed copper foil. The present applicant unexpectedly discovered that when the mass concentration of glucose is 4 g / L and the mass concentration of 40% cyclohexane hexaphosphate is 15-20 mL / L, the addition of inositol (1,4,5) triphosphate, especially when inositol (1,4,5) triphosphate accounts for 20-30% of the mass concentration of cyclohexane hexaphosphate, not only reduces the resistance of the 6-10 μm double-glazed copper foil, but also makes the double-glazed copper foil still bright and discolored when placed at 140°C for 15 minutes (such as the attached Figure 1 As shown in the figure, no light brown spots were produced after being placed in 10% salt spray for 72 hours. It is speculated that the steric hindrance of cyclohexanehexanol hexaphosphate is too large to fill the pores between the passivation films, while the steric hindrance of inositol substances is smaller. The two cooperate with each other to produce a synergistic effect, making the surface of the passivation film denser, while at the same time not making the passivation film too thick to weaken its conductivity.

[0038] A second aspect of the present invention provides an application of a chromium-free passivating agent for copper foil specially used for lithium batteries on copper foil of lithium batteries.

[0039] The passivation method is as follows: dissolve 25-40mL of passivator in 1L of water, stir for 1-2min, immerse 8-12μm copper foil in the passivation solution for 8-12s, take it out, scrape the liquid on the surface of the copper foil with a scraper, and dry it naturally.

[0040] Beneficial effects:

[0041] (1) The chromium-free passivator for copper foil dedicated to lithium batteries of the present invention forms a stable protective film on the surface of 6-10 μm double-glazed copper foil under the synergistic effect of 40% by mass of cyclohexane hexaphosphate, glucose and inositol (1,4,5) triphosphate, thereby reducing the contact between moisture and corrosive substances and the copper foil. The passivated copper foil is placed at a temperature of 140° C. for 15 minutes, and the surface is still bright and does not change color. After being placed in 10% salt spray for 72 hours, no light brown spots are generated, and the conductivity is good, so the copper foil can be applied to the field of lithium ion batteries.

[0042] (2) The chromium-free passivating agent for lithium battery copper foil of the present invention does not use toxic substances such as chromium, arsenic, and selenium, has a simple process, is environmentally friendly, reduces production costs, and is conducive to achieving sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 : Anti-oxidation performance test of the 10 μm double-glazed copper foil in Example 1 after 15 minutes. After 15 minutes, the double-glazed copper foil still has a bright surface and has not changed color. Example

[0044] Example 1

[0045] A chromium-free copper foil passivator for lithium batteries, the preparation raw materials of which include: main salt, organic acid, corrosion inhibitor, chelating agent, complexing agent, additive, organic solvent and inositol substances.

[0046] The main salt is a sodium silicate solution with a mass fraction of 60% and a mass concentration of 15 g / L.

[0047] The organic acid is 40% by mass of cyclohexanehexol hexaphosphate, and the mass concentration is 18 mL / L.

[0048] The corrosion inhibitor is diethanolamine, and the mass concentration is 4 g / L.

[0049] The chelating agent is sodium gluconate with a mass concentration of 5 g / L.

[0050] The complexing agent is hydroxyethylidene diphosphonic acid, and its mass concentration is 0.2 g / L.

[0051] The additives are glucose and zinc oxide, the mass concentration of the glucose is 4 g / L, and the mass concentration of the zinc oxide is 2 g / L.

[0052] The organic solvent is polyethylene glycol 200 with a mass concentration of 10 g / L, purchased from Dow Chemical of the United States, with a CAS number of 25322-68-3.

[0053] The inositol substance is inositol (1,4,5) triphosphate, which accounts for 25% of the mass concentration of cyclohexanehexaphosphate (40% by mass). The inositol (1,4,5) triphosphate was purchased from Kemegen (Shanghai) Biotechnology Co., Ltd. with the product number C110945.

[0054] The preparation method of the chromium-free passivating agent for copper foil of lithium battery is as follows:

[0055] The main salt, organic acid, corrosion inhibitor, chelating agent, complexing agent, additive and organic solvent are added into the reaction kettle according to mass concentration, the stirring speed is 400 rpm / min, and the stirring time is 45 min to obtain the product.

[0056] The present invention also provides an application of a chromium-free passivating agent for copper foil specially used for lithium batteries on copper foil of lithium batteries.

[0057] The passivation method is as follows: dissolve 35 mL of passivator in 1 L of water, stir for 1 min, immerse 10 μm copper foil in the passivation solution for 10 s, take it out, scrape the liquid on the surface of the copper foil with a scraper, and dry it naturally.

[0058] Example 2

[0059] A chromium-free copper foil passivator for lithium batteries, the preparation raw materials of which include: main salt, organic acid, corrosion inhibitor, chelating agent, complexing agent, additive, organic solvent and inositol substances.

[0060] The main salt is a sodium silicate solution with a mass fraction of 60% and a mass concentration of 15 g / L.

[0061] The organic acid is 30% by mass of cyclohexanehexol hexaphosphate, and the mass concentration is 20 mL / L.

[0062] The corrosion inhibitor is diethanolamine, and the mass concentration is 4 g / L.

[0063] The chelating agent is sodium gluconate with a mass concentration of 6 g / L.

[0064] The complexing agent is hydroxyethylidene diphosphonic acid, and its mass concentration is 0.2 g / L.

[0065] The additives are glucose and zinc oxide, the mass concentration of the glucose is 4 g / L, and the mass concentration of the zinc oxide is 2 g / L.

[0066] The organic solvent is polyethylene glycol 200 with a mass concentration of 10 g / L, purchased from Dow Chemical of the United States, with a CAS number of 25322-68-3.

[0067] The inositol substance is inositol (1,4,5) triphosphate, which accounts for 20% of the mass concentration of cyclohexanehexaphosphate (30% by mass). The inositol (1,4,5) triphosphate was purchased from Kemegen (Shanghai) Biotechnology Co., Ltd. with the product number C110945.

[0068] The preparation method of the chromium-free passivating agent for copper foil of lithium battery is as follows:

[0069] The main salt, organic acid, corrosion inhibitor, chelating agent, complexing agent, additive and organic solvent are added into the reaction kettle according to mass concentration, the stirring speed is 400 rpm / min, and the stirring time is 45 min to obtain the product.

[0070] The present invention also provides an application of a chromium-free passivating agent for copper foil specially used for lithium batteries on copper foil of lithium batteries.

[0071] The passivation method is as follows: dissolve 35 mL of passivator in 1 L of water, stir for 1 min, immerse 10 μm copper foil in the passivation solution for 10 s, take it out, scrape the liquid on the surface of the copper foil with a scraper, and dry it naturally.

[0072] Example 3

[0073] A chromium-free copper foil passivator for lithium batteries, the preparation raw materials of which include: main salt, organic acid, corrosion inhibitor, chelating agent, complexing agent, additive, organic solvent and inositol substances.

[0074] The main salt is a sodium silicate solution with a mass fraction of 60% and a mass concentration of 15 g / L.

[0075] The organic acid is 35% by mass of cyclohexanehexol hexaphosphate, and the mass concentration is 15 mL / L.

[0076] The corrosion inhibitor is diethanolamine, and the mass concentration is 4 g / L.

[0077] The chelating agent is sodium gluconate with a mass concentration of 5 g / L.

[0078] The complexing agent is hydroxyethylidene diphosphonic acid, and its mass concentration is 0.2 g / L.

[0079] The additives are glucose and zinc oxide, the mass concentration of the glucose is 2 g / L, and the mass concentration of the zinc oxide is 2 g / L.

[0080] The organic solvent is polyethylene glycol 200 with a mass concentration of 10 g / L, purchased from Dow Chemical of the United States, with a CAS number of 25322-68-3.

[0081] The inositol substance is inositol (1,4,5) triphosphate, which accounts for 25% of the mass concentration of cyclohexanehexaphosphate (35% by mass). The inositol (1,4,5) triphosphate was purchased from Kemegen (Shanghai) Biotechnology Co., Ltd. with the product number C110945.

[0082] The preparation method of the chromium-free passivating agent for copper foil of lithium battery is as follows:

[0083] The main salt, organic acid, corrosion inhibitor, chelating agent, complexing agent, additive and organic solvent are added into the reaction kettle according to mass concentration, the stirring speed is 400 rpm / min, and the stirring time is 45 min to obtain the product.

[0084] The present invention also provides an application of a chromium-free passivating agent for copper foil specially used for lithium batteries on copper foil of lithium batteries.

[0085] The passivation method is as follows: dissolve 35 mL of passivator in 1 L of water, stir for 1 min, immerse 10 μm copper foil in the passivation solution for 10 s, take it out, scrape the liquid on the surface of the copper foil with a scraper, and dry it naturally.

[0086] Example 4

[0087] A chromium-free copper foil passivator for lithium batteries, the preparation raw materials of which include: main salt, organic acid, corrosion inhibitor, chelating agent, complexing agent, additive, organic solvent and inositol substances.

[0088] The main salt is a sodium silicate solution with a mass fraction of 60% and a mass concentration of 15 g / L.

[0089] The organic acid is 40% by mass of cyclohexanehexol hexaphosphate, and the mass concentration is 20 mL / L.

[0090] The corrosion inhibitor is diethanolamine, and the mass concentration is 4 g / L.

[0091] The chelating agent is sodium gluconate with a mass concentration of 5 g / L.

[0092] The complexing agent is hydroxyethylidene diphosphonic acid, and its mass concentration is 0.2 g / L.

[0093] The additives are glucose and zinc oxide, the mass concentration of the glucose is 6 g / L, and the mass concentration of the zinc oxide is 2 g / L.

[0094] The organic solvent is polyethylene glycol 200 with a mass concentration of 10 g / L, purchased from Dow Chemical of the United States, with a CAS number of 25322-68-3.

[0095] The inositol substance is inositol (1,4,5) triphosphate, which accounts for 25% of the mass concentration of cyclohexanehexaphosphate (40% by mass). The inositol (1,4,5) triphosphate was purchased from Kemegen (Shanghai) Biotechnology Co., Ltd. with the product number C110945.

[0096] The preparation method of the chromium-free passivating agent for copper foil of lithium battery is as follows:

[0097] The main salt, organic acid, corrosion inhibitor, chelating agent, complexing agent, additive and organic solvent are added into the reaction kettle according to mass concentration, the stirring speed is 400 rpm / min, and the stirring time is 45 min to obtain the product.

[0098] The present invention also provides an application of a chromium-free passivating agent for copper foil specially used for lithium batteries on copper foil of lithium batteries.

[0099] The passivation method is as follows: dissolve 35 mL of passivator in 1 L of water, stir for 1 min, immerse 10 μm copper foil in the passivation solution for 10 s, take it out, scrape the liquid on the surface of the copper foil with a scraper, and dry it naturally.

[0100] Example 5

[0101] A chromium-free copper foil passivator for lithium batteries, the preparation raw materials of which include: main salt, organic acid, corrosion inhibitor, chelating agent, complexing agent, additive, organic solvent and inositol substances.

[0102] The main salt is a sodium silicate solution with a mass fraction of 60% and a mass concentration of 15 g / L.

[0103] The organic acid is 40% by mass of cyclohexanehexol hexaphosphate, and the mass concentration is 15 mL / L.

[0104] The corrosion inhibitor is diethanolamine, and the mass concentration is 4 g / L.

[0105] The chelating agent is sodium gluconate with a mass concentration of 5 g / L.

[0106] The complexing agent is hydroxyethylidene diphosphonic acid, and its mass concentration is 0.2 g / L.

[0107] The additives are glucose and zinc oxide, the mass concentration of the glucose is 2 g / L, and the mass concentration of the zinc oxide is 2 g / L.

[0108] The organic solvent is polyethylene glycol 200 with a mass concentration of 10 g / L, purchased from Dow Chemical of the United States, with a CAS number of 25322-68-3.

[0109] The inositol substance is inositol (1,4,5) triphosphate, which accounts for 25% of the mass concentration of cyclohexanehexaphosphate (40% by mass). The inositol (1,4,5) triphosphate was purchased from Kemegen (Shanghai) Biotechnology Co., Ltd. with the product number C110945.

[0110] The preparation method of the chromium-free passivating agent for copper foil of lithium battery is as follows:

[0111] The main salt, organic acid, corrosion inhibitor, chelating agent, complexing agent, additive and organic solvent are added into the reaction kettle according to mass concentration, the stirring speed is 400 rpm / min, and the stirring time is 45 min to obtain the product.

[0112] The present invention also provides an application of a chromium-free passivating agent for copper foil specially used for lithium batteries on copper foil of lithium batteries.

[0113] The passivation method is as follows: dissolve 35 mL of passivator in 1 L of water, stir for 1 min, immerse 10 μm copper foil in the passivation solution for 10 s, take it out, scrape the liquid on the surface of the copper foil with a scraper, and dry it naturally.

[0114] Comparative Example 1

[0115] No inositol substance, inositol (1,4,5) triphosphate, was added, the mass fraction of the cyclohexanehexaphosphate solution was changed to 60%, and the rest was the same as in Example 1.

[0116] Comparative Example 2

[0117] The mass concentration of cyclohexanehexanol hexaphosphate was changed to 25 mL / L, inositol (1,4,5) triphosphate accounted for 10% of the mass concentration of cyclohexanehexanol hexaphosphate of 40% by mass, and the rest was the same as in Example 1.

[0118] Comparative Example 3

[0119] The mass concentration of cyclohexanehexol hexaphosphate is changed to 10 mL / L, inositol (1,4,5) triphosphate accounts for 40% of the mass concentration of cyclohexanehexol hexaphosphate, and the rest is the same as in Example 1.

[0120] Comparative Example 4

[0121] The glucose was replaced with sucrose, the mass fraction of the cyclohexanehexol hexaphosphate solution was changed to 20%, and the rest was the same as in Example 1.

[0122] Comparative Example 5

[0123] The mass fraction of the cyclohexanehexol hexaphosphate solution was changed to 20%, the mass concentration of glucose was changed to 8 g / L, and the rest was the same as in Example 1.

[0124] Comparative Example 6

[0125] The mass fraction of the cyclohexanehexol hexaphosphate solution was changed to 60%, the mass concentration of glucose was changed to 1 g / L, and the rest was the same as in Example 1.

[0126] Performance Evaluation

[0127] (1) High-temperature oxidation resistance test: Place the passivated 10 μm double-glazed copper foil in an air-circulating constant temperature box at 140°C. When the temperature of the constant temperature box rises to the specified temperature, start timing. After keeping warm for 15 minutes, observe and record whether there is oxidation discoloration on both sides of the double-glazed copper foil. The longer the recorded time, the better the surface oxidation resistance.

[0128] (2) Salt spray corrosion resistance test: The pH value of the sodium chloride solution is 6.8. The sodium chloride solution is atomized to form a neutral salt spray with a concentration of 10%. The passivated 10μm double-glazed copper foil is placed in a neutral salt spray tester for spray testing. The foil is left to stand for 72 hours. The time it takes for corrosion to appear on the surface of the sample is observed and recorded. The longer the time, the better the salt spray resistance.

[0129] Table 1

[0130]

[0131]

Claims

1. A chromium-free passivator for copper foil for lithium batteries, characterized in that: The raw materials for preparing the copper foil passivator for lithium batteries include: main salt, organic acid, corrosion inhibitor, chelating agent, complexing agent, additive and organic solvent; the organic acid is an organic phosphorus compound, the organic phosphorus compound is a cyclohexane hexaphosphate solution, the volume concentration of the cyclohexane hexaphosphate solution is 15-20 mL / L, and the mass fraction is 40%; the raw materials for preparing the chromium-free passivator for copper foil for lithium batteries also include inositol substances; the inositol substances account for 20-30% of the mass of the organic acid; the inositol substances are inositol (1,4,5) triphosphate; the additive is a polyhydroxy aldehyde, the polyhydroxy aldehyde is glucose, and the mass concentration of the glucose is 4g / L.

2. The chromium-free passivator for copper foil used for lithium batteries according to claim 1, characterized in that: The main salt includes at least one of molybdate, silicate, phosphate, titanium salt, nickel salt and zirconium salt.

3. The chromium-free passivator for copper foil used for lithium batteries according to claim 1, characterized in that: The chelating agent includes at least one of benzotriazole, ethylenediaminetetraacetic acid, sodium gluconate, trisodium nitrilotriacetate and sodium trimethylenephosphonate.

4. The chromium-free passivator for copper foil used for lithium batteries according to claim 1, characterized in that: The additives also include zinc oxide.

5. Use of the chromium-free passivator for lithium battery copper foil according to any one of claims 1 to 4 on lithium battery copper foil.

Citation Information

Patent Citations

  • An electrolytic copper foil surface Chromium-free passivating treatment method

    CN101532154B

Cited By

  • Chromium-free copper corrosion inhibitor with good film-forming stability as well as preparation method and application of chromium-free copper corrosion inhibitor

    CN121781156A